Loss of tau and Fyn reduces compensatory effects of MAP2 for tau and reveals a Fyn‐independent effect of tau on calcium. Issue 11 (26th August 2019) - Liu, Guanghao; Thangavel, Ramasamy; Rysted, Jacob; Kim, Yohan; Francis, Meghan B.; Adams, Eric; Lin, Zhihong; Taugher, Rebecca J.; Wemmie, John A.; Usachev, Yuriy M.; Lee, Gloria
Abstract: Microtubule‐associated protein tau associates with Src family tyrosine kinase Fyn and is tyrosine phosphorylated by Fyn. The presence of tyrosine phosphorylated tau in AD and the involvement of Fyn in AD has drawn attention to the tau–Fyn complex. In this study, a tau–Fyn double knockout (DKO) mouse was generated to investigate the role of the complex. DKO mice resembled Fyn KO in novel object recognition and contextual fear conditioning tasks and resembled tau KO mice in the pole test and protection from pentylenetetrazole‐induced seizures. In glutamate‐induced Ca 2+ response, Fyn KO was decreased relative to WT and DKO had a greater reduction relative to Fyn KO, suggesting that tau may have a Fyn‐independent role. Since tau KO resembled WT in its Ca 2+ response, we investigated whether microtubule‐associated protein 2 (MAP2) served to compensate for tau, since the MAP2 level was increased in tau KO but decreased in DKO mice. We found that like tau, MAP2 increased Fyn activity. Moreover, tau KO neurons had increased density of dendritic MAP2‐Fyn complexes relative to WT neurons. Therefore, we hypothesize that in the tau KO, the absence of tau would be compensated by MAP2, especially in the dendrites, where tau–Fyn complexes are of critical importance. In the DKO, decreased levels of MAP2 made compensation more difficult, thus revealing the effect of tau in the Ca 2+ response. Abstract : The downstream effect of the interaction between microtubule‐associated protein tau and Src family non‐receptor tyrosine kinase Fyn was investigated with a tau/Fyn double KO mouse. We demonstrate that tau has a Fyn‐independent role in glutamate‐induced calcium response and that MAP2 can compensate for tau in interacting with Fyn in dendrites.